Nonlinear Optomechanical Coupling for Ultra-Sensitive Detection of Gravitational Perturbations - Dr. Amarjeet (International Journal of Scientific Research in Science and Technology, 2025)
The detection of weak gravitational signals has traditionally relied on linear optomechanical and interferometric systems, which face intrinsic limitations due to thermal noise and the standard quantum limit. In this work, we propose a nonlinear optomechanical architecture that enhances quantum backaction evasion and significantly improves sensitivity across a broad frequency range. The proposed system is modeled analytically by incorporating nonlinear radiation–pressure coupling and Kerr-type optical nonlinearity, followed by numerical simulations to determine sensitivity thresholds and noise suppression characteristics. Results indicate that the nonlinear design achieves up to an order-of-magnitude improvement in sensitivity over linear counterparts, particularly in the sub-kHz regime relevant for astrophysical sources. Comparative analysis with existing detectors demonstrates the potential of nonlinear coupling in reducing quantum measurement uncertainties and extending the detectable frequency bandwidth. These findings suggest that nonlinear optomechanical systems could play a pivotal role in advancing ultra-sensitive gravitational wave detection and quantum metrology.
Keywords: Nonlinear Optomechanics; Weak Gravitational Signal Detection; Quantum Noise Suppression; Sensitivity Enhancement; Ultra-precise Measurement